Vitamin D Deficiency and Oral Mucositis in Hematopoietic Stem Cell Transplantation: A Cross-Sectional Observation - Kosar Raoufinejad; Shahrzad Pezeshki; Bahram Chahardouli; Molouk Hadjibabaie; Zahra Jahangard-Rafsanjani; Kheirollah Gholami; Mehdi Rajabi; Mohammad Vaezi (Journal of Pharmaceutical Care, 2019)
Backgrounds: One of the most frequent complications of high-dose chemotherapy regimen before hematopoietic stem cell transplantation (HSCT) is oral mucositis (OM). Vitamin D (VD) has well-known immunoregulatory, anti-inflammatory, and antioxidant properties.